BASIC EDUCATION IN THE AI ERA: A CRITICAL ANALYSIS IN A PHILOSOPHICAL PERSPECTIVE - Fitri Oktafiyana; Yusuf Tri Herlambang (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of Artificial Intelligence (AI) has brought significant transformations in basic education, presenting opportunities as well as philosophical and ethical challenges. This research examines the integration of AI in basic learning from a humanistic perspective, with a focus on the development of students' morals, character, and identity. The method used is a qualitative Systematic Literature Review (SLR), examining the literature of the last five years. Thematic and interpretive analysis identified key issues: the ethical use of AI, the role of teachers, student data privacy, school and family collaboration, and curriculum integration. The results show that AI that focuses solely on efficiency risks eroding human values, while a holistic approach that combines cognitive, affective, and social-emotional aspects supports the responsible and humanistic use of AI. This humanistic framework guides teachers, students, and society to create a learning environment that enhances academic achievement while shaping character and social responsibility. In conclusion, the integration of AI in primary education must be accompanied by mature philosophical and ethical reflection so that students develop into academically intelligent, morally mature individuals, and ready to face the challenges of the digital age critically and creatively.